Difference – Identity – Education in a Post – Neoliberal Era: A Call for a New Universalism - Starego, Karolina (INSTED: Interdisciplinary Studies in Education & Society, 2025)
The aim of this paper is the reconstruction of the emergence and dynamics of contemporary identity politics. It argues that the focus on identity is not solely a feature of authoritarian populism but also a feature of meritocratic and individualistic ideology of anti-populist parties and social movements. The paper further explores, how the politicized processes of identity formation manifest as self-victimization, leading to unresolvable culture wars, whose intensity seems to be amplified by the current hegemonic crisis of the neoliberal order. In this context, the article’s main thesis is that, in the face of the twin crises of extreme political polarization and the existential threat posed by the climate crisis, education can play a significant role in establishing new universalism by redirecting attention from the processes of identity formation to the task of generating a new symbolic universe, which would allow the setting aside of the current conflicts.